Lending methodologies and SMEs access to finance in Ghana; the mediating role of credit reference information - Kofi Nyarko Gyimah; Joseph Olorunfemi Akande; Paul-Francois Muzindutsi (Cogent Business & Management, 2022)
A major challenge to SME growth has been access to credit meanwhile literature exploring the effects of lending methodologies on credit access has paid little attention to how credit referencing information can influence the relationship. The study assessed the mediating influence of credit reference information on the interaction between bank lending methodologies and SMEs access to credit in Ghana. Ordinary least square regression analysis was used to analyse 1061 questionnaires collected from businesses in the Accra, Ghana. Results show that two lending methodologies exist both of which impact access to finance with the interaction of credit referencing information enhancing the explanatory power. We concluded that credit referencing plays a role in ensuring that lending methodologies for SMEs access to finance in Ghana is enriched to increase access to credit. The study has implications for policymakers to bring financial technology that ensures financial information can be easily captured from SMEs. This then enhances their creditworthiness for integration into the formal banking system to improve access to credit.
Keywords: 650; access to credit; banking records; credit referencing information; Ghana; Lending methodologies; SMEs